Governance issues for sustainable management of village irrigation in the Dry Zone of Sri Lanka - Imbulana, Upali; Aheeyar, Mohamed M. M.; Amarasinghe, Upali A.; Amarnath, Giriraj (International Water Management Institute, 2023)
Village irrigation systems (ViSs) are vital in rural livelihood, food, and water security. VISs include small (minor) tanks and diversions (anicuts). The hydrologically linked tanks with natural drainage patterns form cascades, and beyond food and water security, they play a significant role in mitigating flood and drought impacts on communities in river basins. With anthropogenic changes, many cascades are in depilated states now. This paper finds that policy support with legal recognition to cascade-based community-level institutions promote bottom-up water and natural resources management approaches. They also facilitate investigations of ill-defined subject areas in cascade management and complex socio-political and economic issues and challenges constraining sustainable cascade based VISs operations.